Evaluating STEM-based Reform Teaching Observation Protocol to Enhance Students’ Communication Skills in the Context of Sustainable Development Goals in Science Learning - Sri Wahyuni; Ilham Batuseng; Nureeyawaji (Jurnal Pendidikan IPA Indonesia, 2024)
STEM-based teaching can be challenging as it requires the integration of science, technology, engineering, and mathematics in one lesson. Selecting an engaging topic involving students’ experiences with current issues can be helpful in this regard. The Sustainable Development Goals (SDGs) are a relevant and impactful topic that may facilitate students’ communication skills. This research aimed to evaluate the Reform Teaching Observation Protocol (RTOP) using a STEM approach to address SDGs and to improve students’ communication skills. This research employed quantitative approach to measure an instrument for teaching STEM through the lens of SDG-related issues in the science learning. The process included creating the items, reviewing the RTOP, and testing these items with participants who are the representatives of the intended users. Exploratory Factor Analysis (EFA) was used to measure the structural correlations among items and topics and assess their internal reliability. The results identified five factors in the RTOP evaluation: developing scientific topics (8 items), skills in conveying specific examples (5 items), use of scientific language terms (2 items), representative forms of scientific evidence (2 items), and involving the STEM approach (2 items). The reliability of the RTOP, as indicated by Cronbach’s Alpha, was 0.818. Based on these findings, the research concludes that the RTOP is both valid and reliable, and can be implemented in the classroom to teach STEM and SDGs, thereby improving students’ communication skills.